1968
DOI: 10.1159/000179632
|View full text |Cite
|
Sign up to set email alerts
|

Etude de la perméabilité du Néphron de l’homme aux électrolytes

Abstract: Le mode d’excrétion des principaux électrolytes a été étudié chez l’homme avec une technique très voisine de celle utilisée par Chinard chez le chien. Après l’injection intra-veineuse rapide d’un indicateur glomérulaire (inuline) et de divers radioisotopes des électrolytes, l’urine urétérale est recueillie par petites fractions. Cette technique permet de séparer nettement la courbe d’apparítion de l’indicateur glomérulaire et celle des électrolytes entrant directement dans les tubes. Pour le K, le Na, le Cl, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1972
1972
1978
1978

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Since Hipparan is both filtered by the glomerulus and also secreted by the proximal tubule, and is not reabsorbed, the transit time of Hippuran closely reflects that of the glomerular filtrate (Schoutens & Raynaud, 1968). This abnormal pattern of transport, which was reversed on treatment in nine out of 14 cases, was associated with lower renal blood flow, more severe hypertension, evidence of left ventricular disease on the ECG, retinopathy and higher PRA values.…”
Section: Discussionmentioning
confidence: 99%
“…Since Hipparan is both filtered by the glomerulus and also secreted by the proximal tubule, and is not reabsorbed, the transit time of Hippuran closely reflects that of the glomerular filtrate (Schoutens & Raynaud, 1968). This abnormal pattern of transport, which was reversed on treatment in nine out of 14 cases, was associated with lower renal blood flow, more severe hypertension, evidence of left ventricular disease on the ECG, retinopathy and higher PRA values.…”
Section: Discussionmentioning
confidence: 99%
“…First, by the autoradiographic evidence of Wedeen (1969) and more directly by the dog studies of Chinard (1956) and the thirty or more studies in man of Schoutens & Raynaud (1968), who found that after injection of PAH and inulin, PAH never appeared at the ureter more than a few seconds before inulin. This does not necessarily imply that the pulse-input renogram will have a horizontal first portion, as the intrarenal transport may affect the observed count rate.…”
Section: Discussionmentioning
confidence: 99%
“…In every case this composite function, H,(t)+H,(t), which is determined jointly by both venous and urinary outflow of Hippuran, shows a sharp initial fall. This is assumed to represent the vascular outflow function H&) over the first minute of the test, since there is a minimum delay of at least 75 s associated with the passage of Hippuran or of PAH through tubular cell and nephron (Chinard, 1956;Wedeen, 1969;Schoutens & Raynaud, 1968). Differentiation of the complete function after inversion yields the overall spectrum of transit times h,(t) +h,(t), and an example from a study on a normal subject is shown in Fig.…”
Section: Theory and C O M P U T A T I O N Smentioning
confidence: 99%
See 1 more Smart Citation